Clinical Symptoms, Diagnose, Dental Implication and Management of Bell's Palsy: Review - Susanna Halim; Sharon Altin Taqwani (Pascasarjana, Mataram University, 2025)
Bell’s palsy is an acute peripheral facial nerve paralysis that causes sudden unilateral facial weakness and remains a common neurological condition. This study aimed to review recent literature related to the clinical features, diagnosis, etiology, classification, and management of Bell’s palsy, especially its implications in dental practice, using a literature review approach from international journals published within the last five years. The results showed that the diagnosis of Bell’s palsy is primarily clinical, supported by physical examination and selective investigations such as EMG and MRI. Corticosteroids remain the main treatment, while antivirals and physiotherapy are beneficial in selected cases. Most patients experience significant recovery within several months with appropriate management. In conclusion, early diagnosis and combination therapy, supported by proper rehabilitation and dental care, play an important role in improving recovery and preventing complications in patients with Bell’s palsy